Kesalahan Morfologis pada Teks Ceramah Peserta Didik Kelas XI SMA - Metriana Putri; Ika Septiana; R. Yusuf Sidiq Budiawan (Jurnal Kualita Pendidikan, 2021)
This study aims to describe morphological errors and the causes of morphological errors in lecture texts by class XI students of SMA Negeri 1 Mranggen in the 2020/2021 academic year. The data collection method used in this research is the documentation method with the see techniques and note techniques as well as the interview method. The research used used mixed methods by combining qualitative data, then followed by quantitative data as supporting data. The technique for presenting the results of the analysis in this study uses informal techniques, namely pouring out the results of the analysis by outlining the data that has been obtained in the form of morphological errors in the lecture texts of class XI students of SMA Negeri 1 Mranggen in the 2020/2021 school year and the causes of these errors. The results of data analysis will be presented in a descriptive form. The results of this study indicate that there are language errors of morphological types consisting of affixation errors of transitive verbs, prefixes meng-, prefixes ber-, suffixes -kan, and suffixes -i, affixation errors of intransitive verbs prefixes ber- and prefixes ter-, to word errors. compound. The factors causing morphological errors were also found, namely lack of understanding of the structure and writing rules, difficulty in choosing the right words, lack of understanding of words with affixes or compound words, and being influenced by the first language or mother tongue.